Redox Homeostasis and Cellular Antioxidant Systems: Crucial Players in Cancer Growth and Therapy. (21st June 2016) - Marengo, Barbara; Nitti, Mariapaola; Furfaro, Anna Lisa; Colla, Renata; Ciucis, Chiara De; Marinari, Umberto Maria; Pronzato, Maria Adelaide; Traverso, Nicola; Domenicotti, Cinzia
Abstract : Reactive oxygen species (ROS) and their products are components of cell signaling pathways and play important roles in cellular physiology and pathophysiology. Under physiological conditions, cells control ROS levels by the use of scavenging systems such as superoxide dismutases, peroxiredoxins, and glutathione that balance ROS generation and elimination. Under oxidative stress conditions, excessive ROS can damage cellular proteins, lipids, and DNA, leading to cell damage that may contribute to carcinogenesis. Several studies have shown that cancer cells display an adaptive response to oxidative stress by increasing expression of antioxidant enzymes and molecules. As a double-edged sword, ROS influence signaling pathways determining beneficial or detrimental outcomes in cancer therapy. In this review, we address the role of redox homeostasis in cancer growth and therapy and examine the current literature regarding the redox regulatory systems that become upregulated in cancer and their role in promoting tumor progression and resistance to chemotherapy.